2011
DOI: 10.1007/s10765-011-1019-6
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Temperature Drop for High-Temperature Fixed Points for Different Furnace Conditions

Abstract: High-temperature fixed points (HTFPs) based on eutectic and peritectic reactions of metals and carbon are likely to become, in the near term, reference standards at high temperatures. Typically for radiation thermometry applications, these HTFPs are generally formed of a graphite crucible, with a reentrant well, an included 120 • cone, and a nominal aperture of 3 mm. It is important to quantify the temperature drop at the back wall of the cavity, and to understand the influence of the crucible configuration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 4 publications
(4 reference statements)
0
20
0
Order By: Relevance
“…From the Re-C temperature drop values some implications can be drawn, referenced in previous studies [6]. The lowest values correspond to the VNIIOFI (no.…”
Section: Temperature Drop Estimatesmentioning
confidence: 72%
See 2 more Smart Citations
“…From the Re-C temperature drop values some implications can be drawn, referenced in previous studies [6]. The lowest values correspond to the VNIIOFI (no.…”
Section: Temperature Drop Estimatesmentioning
confidence: 72%
“…It is anticipated that these are extreme cases and that the actual furnace temperature profile likely lies between these two. Earlier work [6] has shown that the actual profile itself does not have a significant influence on the resultant estimated temperature drop values. The temperature profile is maintained in shape, but scaled in value for different transition temperatures.…”
Section: Temperature Drop Calculationsmentioning
confidence: 92%
See 1 more Smart Citation
“…This is computational fluid dynamics (CFD) software which uses a finite volume method (FVM) to solve numerically a simplification of the equations that govern the physical problem in each volume in which the geometry is divided. This method was used in previous studies in this field [3]. The model describes the heat transport in a transient state during the freezing of the fixed point.…”
Section: Introductionmentioning
confidence: 99%
“…In the impure system, described by an effective Scheil function, in any case two-front melting was induced, the evolution of the fronts with time depends on the impurity level and the heat injection rates. The cell was represented by an axisymmetrical model [6,7] with heat injection and extraction rates as boundary conditions. As shown in Fig.…”
Section: Introductionmentioning
confidence: 99%